Lower extremity artery disease in patients with type 2 diabetes - Buso, Giacomo; Aboyans, Victor; Mazzolai, Lucia (European journal of preventive cardiology, 2019)
Among all peripheral arterial diseases, lower extremity arterial disease is a serious condition in subjects with type 2 diabetes mellitus, associated with important disability, cardiovascular risk, and socio-economic burden. Patients with both conditions generally display poorer prognosis of affected limbs compared with non-diabetic subjects, leading to increased rates of adverse limb events including amputations. Nonetheless, awareness on lower extremity arterial disease remains somehow suboptimal in the diabetic population, partly related to an atypical clinical presentation in several cases. A regular and appropriate screening for lower extremity arterial disease in patients suffering from type 2 diabetes mellitus is therefore recommended. Affected subjects should receive optimal medical treatment including careful management of the different cardiovascular risk factors through a healthy lifestyle, a regular and structured physical activity, the administration of lipid-lowering, antidiabetic drugs, and (when indicated) antihypertensive and antithrombotic drugs. This review aims to outline current evidence about lower extremity arterial disease in patients with type 2 diabetes mellitus, in order to elucidate its epidemiology, pathophysiology, screening and diagnosis, and management options.